Intergenerational effects of the pre-conception period on the number of services required by the daughter in dairy cows - Abdelkader A. Ameur; Roger I. Cue; Marc-André Sirard (PLoS ONE, 2026)
This study investigated how the metabolic status of dairy cow dams during the pre-conception period influences the fertility of their daughters. Using a large dataset from Lactanet Canada (2008–2023), we analyzed whether cumulative milk yield deviations—used as a proxy for energy balance—during the 40 days before conception were associated with the number of services required for conception across four daughter lactations. A linear mixed model incorporating milk yield deviations was employed. Results showed that daughters of high-yielding dams required more services (2.25) compared to those of low-yielding dams (2.15), suggesting impaired fertility associated with elevated maternal production. Additionally, daughters of multiparous dams required fewer services, indicating potential selection for fertility with increasing dam lactation number. Days in milk (DIM) at dam conception were positively associated with the number of services required by daughters in their first lactation. Overall, daughters in their first lactation required fewer services than those in subsequent lactations, reflecting a decline in reproductive efficiency with age. These findings highlight the influence of maternal metabolic status on offspring fertility, emphasizing the importance of managing dam energy balance during the preconception period to enhance herd reproductive performance.